Cell-targeted c(AmpRGD)-sunitinib molecular conjugates impair tumor growth of melanoma. (1st April 2019) - Bianchini, Francesca; Portioli, Elisabetta; Ferlenghi, Francesca; Vacondio, Federica; Andreucci, Elena; Biagioni, Alessio; Ruzzolini, Jessica; Peppicelli, Silvia; Lulli, Matteo; Calorini, Lido; Battistini, Lucia; Zanardi, Franca; et al.
Abstract: Drug resistance and off-organ toxicity remain unsolved issues in chemotherapy of advanced-stage melanoma patients. Thus, the creation of new molecular conjugates able to combine a selective accumulation, high ability of internalization and signaling pathway inhibition, are highly requested. Recently, we reported a new class of molecular conjugates, compounds1 –3, where the anti-αV β3 integrin peptidomimetic c(AmpRGD), which is a selective ligand for αV β3 integrin, was covalently bound to the tyrosine kinase inhibitor sunitinib. Here, we report that these c(AmpRGD)-sunitinib conjugates and, in particular, compound3, are selectively internalized by human melanoma cells through αV β3 receptor-mediated endocytosis. Compound3 is more effective than sunitinib in reducing in vitro melanoma cells proliferation, cloning efficiency, migration, and invasion. More interestingly, compound3 is able to significantly reduce the growth of xenografted melanoma tumor developed in immune-compromised mice, more efficiently than an equimolar dose of sunitinib. Indeed, its targeting ability was demonstrated by the selective localization at the tumor level with respect to healthy tissues. Thus, c(AmpRGD)-sunitinib conjugates such as compound3 could serve as intriguing multiple-target agents to selectively reach melanoma cells and interfere with the progression of the disease. Highlights: c(AmpRGD)-sunitinib conjugates were developed in view to reduce drug resistance and off-organ toxicity in cancer. c(AmpRGD)-sunitinib compound 3 selectively enters melanoma cells by recognition of αV β3 integrin receptors. c(AmpRGD)-sunitinib compound 3 reduces xenografted melanoma growth and preferentially accumulates in the tumor tissue. The use of RGD-targeted conjugates represents an appealing approach toward enhanced drug efficacy at a lowered drug dosage.